Rehabilitation of a Partial Nasal Defect with Facial Prosthesis: A Case Report - Ramin Negahdari; Alireza Pournasrollah; Sepideh Bohlouli; Alireza Sighari Deljavan (Tabriz University of Medical Sciences, 2014)
Malignancies of the midface result in cosmetic deformities that make maxillofacial prosthesis as an integral part of the treatment plan. Facial defects can be devastating in their impact on physical structure and function of the affected individual, leading to potentional compromises in quality of life. Reconstruction of nasal defects is a challenge for the prosthodontist because of esthetic and retention problems associated with the facial prosthesis. This paper reports the rehabilitation of a partial nasal defect caused by basal cell carcinoma treatment using a nasal prosthesis made with silicone elastomers and mechanical and anatomical retentive aids. The patient had no problem with the prosthesis, except for a partial loss of extrinsic coloration in the two-year follow-up.